Safety of the insect repellent N,N-diethyl-M-toluamide (DEET) in pregnancy. - Mcgready, R; Hamilton, K; Simpson, J; Cho, T; Luxemburger, C; Edwards, R; Looareesuwan, S; White, N; Nosten, F; Lindsay, S (2001)
The safety of daily application of N, N-diethyl-m-toluamide (DEET) (1.7 g of DEET/day) in the second and third trimesters of pregnancy was assessed as part of a double-blind, randomized, therapeutic trial of insect repellents for the prevention of malaria in pregnancy (n = 897). No adverse neurologic, gastrointestinal, or dermatologic effects were observed for women who applied a median total dose of 214.2 g of DEET per pregnancy (range = 0-345.1 g). DEET crossed the placenta and was detected in 8% (95% confidence interval = 2.6-18.2) of cord blood samples from a randomly selected subgroup of DEET users (n = 50). No adverse effects on survival, growth, or development at birth, or at one year, were found. This is the first study to document the safety of DEET applied regularly in the second and third trimesters of pregnancy. The results suggest that the risk of DEET accumulating in the fetus is low and that DEET is safe to use in later pregnancy.